Rispekt a Fool to Avoid Noyze : Emboozi z'omu Ttakisi z'e Kampala - Kainempisa, Katana (Uganda : Davina Philomena Kiwanuka, 2024)
rispekt a fool to avoid noyze : emboozi z'omu ttakisi ze kampala is a collection of stories set in the 14-seater minibuses (also known as passenger service vans, kamunye, matatu, taxis, etc), typically toyota hiace models, widely used for public transportation in uganda. originally shared as whatsapp status updates, these stories are from an archive spanning late 2019 to early 2024. using conventional and experimental formats, they explore the everyday and everynight experiences of community across the greater kampala metropolitan area.